Analisis Produksi Bahan-Bahan Perkerasan Jalan Untuk Hotmix AC-WC - Mekar Ria Pangaribuan; Dafrin Dafrin (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2020)
Abstract Aggregate is a construction material that has an important role in the activities of highway construction. As the main constituent of pavement material, the proportion of aggregate in a mixture of 90-95 % by weight of pavement either flexible or rigid pavement pavement The purpose of the examination materials derived from laboratory to one production stone crusher machine in the villageGunung selan, is to determine the quality of material of each aggregate for admixture asphalt concrete wearing course (AC-WC). This result are in the experiment marshall, Stability of 10 (ten) of the test substance over a minimum standard stability properties Laston mixture (AC), and for the melting of 10 ( ten ) test materials, test material Number 3A+SA+SB in excess of the maximum,standard (2-4), the results of the experiment marshall melting of the material that is 3A = 4.2 mm, 5A and SB = 6.2 = 4.7 which exceeds the maximum melting tersbut likely caused by the lack of the number.